Cholesterol absorption blocker ezetimibe prevents muscle wasting in severe dysferlin‐deficient and mdx mice. Issue 1 (19th December 2021) - White, Zoe; Theret, Marine; Milad, Nadia; Tung, Lin Wei; Chen, William Wei‐Han; Sirois, Martin G.; Rossi, Fabio; Bernatchez, Pascal
Abstract: Background: Muscular dystrophy (MD) causes muscle wasting and is often lethal in patients due to a lack of proven therapies. In contrast, mouse models of MD are notoriously mild. We have previously shown severe human‐like muscle pathology in mdx [Duchenne MD (DMD)] and dysferlin‐deficient limb‐girdle MD type 2B (LGMD2B) mice by inactivating the gene encoding for apolipoprotein E (ApoE), a lipid transporter synthesized by the liver, brain and adipocytes to regulate lipid and fat metabolism. Having recently established that human DMD is a novel type of primary genetic dyslipidaemia with elevated cholesterol, we sought to determine whether cholesterol could exacerbate the muscle wasting process observed in severe rodent MD. Methods: Severe mdx and dysferlin knock‐out mice lacking ApoE were treated with ezetimibe (15 mg/kg/day), a clinically approved drug exhibiting few pleiotropic effects. In separate studies, dietary cholesterol was raised (from 0.2% to 2% cholesterol) in combination with experimental micro‐injury and direct cholesterol injection assays. Muscles were assessed histologically for changes in collagen and adipocyte infiltration and both transcriptomic and cellular changes by RNA‐seq and fluorescence‐activated cell sorting analysis. Results: Treatment of severe DMD and LGMD2B mice with ezetimibe completely prevented clinical signs of ambulatory dysfunction (0% incidence vs. 33% for vehicle treatment; P  < 0.05). Histological analyses revealed that ezetimibe‐reduced fibro‐fatty infiltration up to 84% and 63% in severely affected triceps ( P  ≤ 0.0001) and gastrocnemius ( P  ≤ 0.003) muscles, resulting in a respective 1.9‐fold and 2.2‐fold retention of healthy myofibre area ( P  ≤ 0.0001). Additionally, raising dietary cholesterol and thus concentrations of plasma low‐density lipoprotein‐associated cholesterol (by 250%; P  < 0.0001) reduced overall survivability (by 100%; P  < 0.001) and worsened muscle damage in the LGMD2B triceps by 767% ( P  < 0.03). Micro‐pin‐induced mechanical injury in LGMD2B mice fed a high cholesterol diet exacerbated muscle damage by 425% ( P  < 0.03) and increased macrophage recruitment (by 98%; P  = 0.03) compared with those injured on a chow diet. Parallel RNA‐seq analyses revealed that injury in cholesterol‐fed mice also modulated the expression of 3671 transcripts (1953 up‐regulated), with fibrogenic, inflammatory and programmed cell death‐associated pathways among the most enriched. Mice lacking dysferlin also displayed heightened muscle necrosis (by 123%; P  < 0.0001) following a direct intramuscular injection of cholesterol compared with control mice. Conclusions: Cholesterol exacerbates rodent MD. Specific inhibition of cholesterol absorption with ezetimibe may safely attenuate human MD severity and delay death.